Investigating discursive functions and potential cognitive demands of teacher questioning in the science classroom. (2nd July 2020) - Soysal, Yılmaz
ABSTRACT: This study presents an in-depth exploration of the types of discursive functions of teacher questioning and the potential cognitive correspondences embedded in the questioning. The participants were a science teacher and his class of 26 sixth-grade students who were engaged in an immersion science inquiry activity. The major data source was a video recording of the class that was analysed through systematic observation in two phases: coding and counting. Five higher-order categories (predicting, communicating, challenging, legitimising, and managing the discourse) and several sub-categories were abstracted for the discursive functions of teacher questioning. Particular discursive functions of teacher questioning attached to the specific potential cognitive demands embedded in the questioning are explored in detail according to the Bloomian taxonomy (i.e., predicting > understand; communicating > understand; challenging > evaluate; legitimising > evaluate; managing the discourse > analyse). From the data, recommendations were offered for science teachers, teacher educators, and the envisagement and implementation of professional development programmes centralising teacher questioning.